2010
DOI: 10.1016/j.burns.2009.06.211
|View full text |Cite
|
Sign up to set email alerts
|

A microarray analysis of temporal gene expression profiles in thermally injured human skin

Abstract: Partial-thickness burn injuries incite a multitude of responses which eventually culminate in cutaneous wound repair. We hypothesized that these events would evoke extensive alterations in gene expression thereby orchestrating the complexity of spatial and temporal events that characterize “normal” human wound healing. In the present study, gene expressions from partial-thickness areas at defined temporal periods (1-3 days, 4-6 days, and 7-18 days) after injury were compared to normal non-wounded skin. Gene al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 44 publications
(51 reference statements)
1
43
0
Order By: Relevance
“…27 In addition, S100A12 was highly expressed in hypertrophic scar, 28 which occurs commonly after deep partial-thickness burns. And, S100A12 expression was elevated from postburn day 0-17 in the margins of partialthickness burn wounds in a clinical study 29 ( Fig. 3).…”
Section: Burn Injury Progressionmentioning
confidence: 88%
“…27 In addition, S100A12 was highly expressed in hypertrophic scar, 28 which occurs commonly after deep partial-thickness burns. And, S100A12 expression was elevated from postburn day 0-17 in the margins of partialthickness burn wounds in a clinical study 29 ( Fig. 3).…”
Section: Burn Injury Progressionmentioning
confidence: 88%
“…Their results demonstrated dramatically different reactions to injury between skin and mucosal wounds. 19 In a study by Greco et al, 20 the gene expression profiles of thermally injured human skin were observed with microarrays. For the analysis, skin samples were…”
Section: Human Wound-healing Microarray Studiesmentioning
confidence: 99%
“…Greco et al found that the expressions of several hundreds of genes were significantly altered between groups, including many calcium-binding proteins, cytokeratins, and chemokines. 20 In one study, Deonarine et al 21 investigated gene expression changes in skin wounds by collecting punch biopsies before and after wounding from basal cell carcinoma patients. They concluded that the initial response to a cutaneous wound induces transcriptional activation of proinflammatory stimuli which may alert the host defense.…”
Section: Wide-scale Platforms In Clinical Wound-healing Researchmentioning
confidence: 99%
“…8d). Among 179 genes elevated by IMQ in 129/SvJ females, for example, 82 were correspondingly increased in burn wound margins (0-3 days post-injury) [51], whereas fewer (53) were elevated in psoriasis lesions (Fig. 8e).…”
Section: Imq Treatment Of Molf Males Induces Tlr Gene Expression But mentioning
confidence: 99%
“…Additional datasets incorporated into analyses include those from prior microarray studies of IMQ dermatitis in mice (GSE27628, GSE47607, GSE60804, GSE63684, GSE78057) [2,[20][21][22], human KCs treated with poly(I:C) (GSE21260) [46], human KCs treated with IL-17A (GSE12109, GSE24767, GSE27533, GSE32620, GSE36287, GSE52361, GSE53751), the Immunological Genome Project (IGP; GSE15907) [47,48], macroscopically normal human skin from control subjects without skin disease (n = 90 subjects; GSE54456; Additional file 2), laser capture microdissected human suprabasal and basal epidermis (GSE42114) [49], regenerated human epidermis organotypic cultures (GSE52953) [50], Mediterranean spotted fever eschars (GSE32993), burn wound margins 0-3 days post-injury (GSE8056) [51], and Leishmania braziliensis-infected cutaneous lesions (GSE55664) [52]. Comparisons to 35 human skin diseases were made using a database of 124 expression signatures compiled and described in a previous publication [45].…”
Section: Additional Gene Expression Datasetsmentioning
confidence: 99%